Coenzyme Q10 supplementation in traumatic brain injury: a scoping review protocol. (September 2019) - Allan, Kaylee; Hayes, Kati; Thomas, Matt; Barnard, Katie
ABSTRACT: Objective: The objective of this review is to map evidence on coenzyme Q10 (CoQ10) use in traumatic brain injury (TBI). Introduction: Traumatic brain injury is an insult to the brain structure caused by external force and resulting in physiological disruption to brain function. Globally, 60% of all TBIs occur from road traffic accidents. In 2016, the World Health Organization reported that road traffic accidents were among the top 10 leading causes of death. Following the initial brain injury, a secondary injury can occur due primarily to a significant increase in production of free radicals causing oxidative stress, which can dictate the patient's ability to survive. Coenzyme Q10 is known to protect neuronal cells from oxidative stress; the mechanism for this has been examined in studies using rats. This review will examine what is known about CoQ10 in TBI and identify gaps in the literature, which may guide future research. Inclusion criteria: The review will include both human and animal subjects who have experienced a TBI in the acute/laboratory-controlled setting and where CoQ10 is supplemented. Animal studies will be included. The review will consider experimental and quasi-experimental study designs including randomized controlled trials, non-randomized controlled trials, before and after studies, and interrupted time-series studies. Studies published in English will be considered, with no date restriction. Methods: Searches will be conducted in the Cochrane Library, MEDLINE, Embase, CINAHL and trial registries. Data will be extracted and presented on details about the population, concept, context, study methods and key findings.